Detection, expression and elucidation of the mechanism of action of mitochondrial uncoupling Protein 1 - Breen, Eamon Patrick (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2006)
A system for overexpression of recombinant proteins in E. coli is defined. Using subcloning techniques the cDNAs for human uncoupling proteins (hUCP) 1, 2 and 3 were introduced to the pET expression system for E. coli. Inducible expression is conferred upon the bacteria. Expression of hUCP2 and hUCP3 was possible in the commonly used strain of expression bacterium E. coli BL21 pLysS. However, hUCP1 was not expressed in these bacteria. A codon bias for human mRNA codons was investigated using the BL21 Codon-Plus strain which has only three under-represented codons, but expression failed. However, using the BL21 derivative strain Rosetta pLysS, which possess all under-represented human codons on the pRARE plasmid, expression of hUCP1 was possible. Codon bias was obviously a problem for expression of hUCP1 in BL21 pLysS and BL21 Codon-Plus E. coli. All UCPs expressed w ere accumulated in inclusion bodies as aggregated proteins.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin